The emergence of statistical science - Ostasiewicz, Walenty (Silesian Statistical Reviev, 2014)
In this short note the origin of the word “statistics” is explained. Girolamo Ghilini was the first who used that word in 1663. G. Achenwall coined the artificial word “Statistik”, not existing in German language, and used it to name the science about states. Scotsman J. Sinclair stolen this word from German and introduced into English. K. Pearson, expressing the gratitude for Sinclair, said that we had to bless this robbery
Śląski Przegląd Statystyczny = Silesian Statistical Review, 2014, nr 12 (18), s. 75-81
Keywords: history of statistics; Achenwall; Ghilini